2021
DOI: 10.1093/bbb/zbab029
|View full text |Cite
|
Sign up to set email alerts
|

Fusobacterium nucleatum impedes remission of colitis in a mouse model

Abstract: The role of Fusobacterium nucleatum, often associated with intestinal diseases, in remission of dextran sulfate sodium (DSS)-induced colitis was investigated. Female mice were divided into groups DC (DSS control) and DF (DSS + F.nucleatum). F.nucleatum (1.0 × 1010 cfu/mouse/day) in PBS was orally given to DF, while DC had PBS only. All mice had DSS in drinking water. In Experiment 1, mice underwent two inflammation phases, an in-between recovery phase, and had their disease activity indices (DAI) calculated. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Regarding F. nucleatum, it is a common member of the oral core microbiome; however, because of its proinflammatory potential, it has been associated with various periodontal diseases, with its increase also related to the severity of disease and the progression of inflammation [58]. Furthermore, F. nucleatum has been detected as being significantly enriched in the gut in IBD and UC subjects [4,59,60], being related even to the promotion of colitis, its aggravation, and the impediment of the remission [61][62][63], as well as having been found to cause opportunistic infections, and to be associated with colorectal cancer and IBD [64].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding F. nucleatum, it is a common member of the oral core microbiome; however, because of its proinflammatory potential, it has been associated with various periodontal diseases, with its increase also related to the severity of disease and the progression of inflammation [58]. Furthermore, F. nucleatum has been detected as being significantly enriched in the gut in IBD and UC subjects [4,59,60], being related even to the promotion of colitis, its aggravation, and the impediment of the remission [61][62][63], as well as having been found to cause opportunistic infections, and to be associated with colorectal cancer and IBD [64].…”
Section: Discussionmentioning
confidence: 99%
“…Vibrio is pathogenic to the gastrointestinal tract, particularly in immunocompromised individuals ( 59 , 60 ). Fusobacterium was reported to easily impede colitis remission in mice ( 61 ). Anaerobiospirillum succiniciproducens is a rare cause of bacteremia in humans and can cause intestinal infection ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, these indicators were significantly lower in the PNE100 group than in the CON, PNE200, and PNE400 groups. These serum parameters were positively correlated with Anaerobiospirillum ( 62 ), Vibrio ( 59 ), Fusobacterium ( 61 ), and Shewanella ( 58 ), which are infectious pathogens. To the best of our knowledge, no study has reported the effects of pine needles on poultry intestinal flora, particularly in laying hens.…”
Section: Discussionmentioning
confidence: 99%
“…15 Studies have shown that the elevated presence of F. nucleatum in colon can imped colitis remission and promote the initiation, progression, and metastasis of colorectal cancer. 10,35 Here, we established a F. nucleatum and DSS-coinduced UC mice model and demonstrated that chronic KS treatment ameliorated this colitis murine model. Consistent with reported studies, the increasing abundance of F. nucleatum aggravated the clinical symptoms of DSS-induced colitis.…”
Section: Ros-scavenging Effectmentioning
confidence: 97%